If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + 15 = 2 Reorder the terms: 15 + w = 2 Solving 15 + w = 2 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + w = 2 + -15 Combine like terms: 15 + -15 = 0 0 + w = 2 + -15 w = 2 + -15 Combine like terms: 2 + -15 = -13 w = -13 Simplifying w = -13
| 1-7y=2y-14 | | (2x)(x+4)=0 | | 5t+4r+9=0 | | 9+3.5f=11-0.5g | | 36+2y=-4y | | 5x+9-3x=0 | | X^2-4x-k+4=0 | | x+73=4961 | | 29-y=37 | | 5x+9=11x-27 | | (x)(4x+5)=520 | | 2y=-3x+29 | | -7x+9=19-3x | | -2y-3y+9=4-3-y | | 600=300+10c | | X^2-12x+49=22 | | 13y+2=9y+22 | | 97b=2037 | | 14x-9x=7 | | 11n^2=5n^2 | | 16b=128 | | 600=5s+400 | | x-.16x=543.90 | | 11x-4=117 | | x-.16=543.90 | | 600=175+10c | | 4n-3=4n-3 | | 4y^2+36y+72=0 | | 5/4(a-8=2/3 | | 3x[x-3]=6 | | 600=50+10c | | 7y-3y=18 |